Analysis of Position Error in Offset Slider Crank Mechanism - R, Chetana; T.V. Vineeth Kumar (Journal of Mines, Metals and Fuels, 2023)
Four-bar linkage mechanisms have attracted much attention for the mobility of equipment’s and devices. The offset slider crank mechanism is an inversion of four-bar mechanism, where the slider will move at a offset distance from the rigid link. In the assembly and mobility of heavy equipment such as satellites, offset slider crank mechanism is used as ground support equipment. In this study, the mechanism is analyzed for the influence of deviations in input parameters on mechanical performance. The slider position depends on the crank angle (Ø), crank length (l), the connecting rod length (r) and slider offset (e). The error in the slider displacement with variable input parameters was expressed analytically and solved using the MAT LAB program. The result can depict the error in slider displacement and the quantification of the input error on it. Thus, it highlights the influence of input parameters and facilitates in predicting the effective and precise motion of the mechanism.